2011
DOI: 10.1029/2010wr009714
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical evidence for intrinsic nonmigrating bars in alluvial channels

Abstract: [1] Alternate bars in straight alluvial channels are migrating or nonmigrating. The currently accepted view is that they are nonmigrating if the width-to-depth ratio is at the value of resonance or if the bars are forced by a persistent local perturbation. We carried out 2-D numerical computations and a long-duration mobile-bed flume experiment to investigate this view. We find that nonmigrating bars can also occur in straight channels without resonant width-to-depth ratio or steady local perturbation. They ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
85
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 28 publications
11
85
0
Order By: Relevance
“…6A, B, 7A, B, and 12). Similar bar-bank interaction were observed in field (Leopold et al, 1964;Klösch et al, 2015) and in laboratory and numerical experiments (Crosato et al, 2011;van de Lageweg et al, 2014) and is typical for the bend apex section of meandering rivers (Luchi et al, 2012). The peak variation of the bar area within the slug was connected with bend development (Figs.…”
Section: Controls Of the Temporal And Spatial Development Of The Backsupporting
confidence: 76%
See 1 more Smart Citation
“…6A, B, 7A, B, and 12). Similar bar-bank interaction were observed in field (Leopold et al, 1964;Klösch et al, 2015) and in laboratory and numerical experiments (Crosato et al, 2011;van de Lageweg et al, 2014) and is typical for the bend apex section of meandering rivers (Luchi et al, 2012). The peak variation of the bar area within the slug was connected with bend development (Figs.…”
Section: Controls Of the Temporal And Spatial Development Of The Backsupporting
confidence: 76%
“…This highlighted the role of large floods in slug development and suggested that during future periods without large floods the slug magnitude will be stable and that the channel bend curvature in the slug section will be increased (similarly as in 2003-2012; Fig. 7B) as a result of bar development at a fixed location (Leopold et al, 1964;Crosato et al, 2011;van de Lageweg et al, 2014). Another future scenario in a period with flood magnitude lower than that in the period 2003-2012 may also be assumed.…”
Section: Controls Of the Temporal And Spatial Development Of The Backmentioning
confidence: 91%
“…Another possibility for non migrating bars in straight channel is that K reached its resonance value [4]. Crosato et al [13], Lisle et al [38] also found that non-migrating bars can be an intrinsic response of the alluvial river bed for coarse mixed-sized sediments and if the bank erosion rates are very low.…”
Section: Introductionmentioning
confidence: 94%
“…Woody pioneer vegetation can recruit or sprout on two general types of alluvial bars, namely free (or migrating) and forced (nonmigrating) bars (see review in Rodrigues et al, 2015). Nonmigrating bars (e.g., point bars, mid-channel bars) correspond to sediment accumulation developing due to a discontinuity in the channel geometry (Olesen, 1984;Struiksma et al, 1985;Parker and Johanneson, 1989;Crosato et al, 2011), while free bars arise because of morphodynamic instability (Tubino, 1991;Tubino et al, 1999). Since the latter are rather unstable and rapidly migrating units (Claude et al, 2014), the development of vegetation and its resistance to physical stresses on these macroforms is rare.…”
Section: Introductionmentioning
confidence: 99%
“…Since the latter are rather unstable and rapidly migrating units (Claude et al, 2014), the development of vegetation and its resistance to physical stresses on these macroforms is rare. Contrarily, because of their conditions of formation, nonmigrating bars are relatively stable units on which woody vegetation can recruit and survive even in morphologically very active rivers (Nakayama et al, 2002;Charron et al, 2011;Crouzy et al, 2013). Large woody debris and vegetation can sometimes trigger a local nursing effect interesting for the development of other seedlings (Gurnell et al, 2005).…”
Section: Introductionmentioning
confidence: 99%